Saving management from our obsession with leadership - Detert, James R.; Kniffin, Kevin; Leroy, Hannes (MIT Sloan Management Review, 2022)
Organizations and top teams downplay or ignore how hard it is to be a good manager — to skillfully hire, engage, develop, coach, supervise, evaluate, and promote people. Most managers aren’t held accountable for building and exercising these critical skills. Instead, they’ve internalized the strong message that qualities like strategic vision and executive presence matter much more, leaving them and their organizations poorly equipped to deal with reality. Here are the skills that can turn the tide.